Storage Stability of Nutritional Qualities, Enzyme Activities, and Volatile Compounds of “Hangjiao No. 2” Chili Pepper Treated With Different Concentrations of 1-Methyl Cyclopropene - Bakpa, Emily Patience; Zhang, Jing; Xie, Jianming; Ma, Yufeng; Han, Kangning; Chang, Youlin (Frontiers in Plant Science, 2022)
The aim of this study was to determine the effects of different concentrations of 1-methylcylopropene (1-MCP) on the nutritional quality, antioxidant enzyme activities and volatile compounds of 'Hangjiao No.2' chili pepper during 12 days storage at ambient temperature. The chili fruit were randomly selected and divided into four groups corresponding to the four treatments, thus 0.5, 1.0 and 1.5 µL L-1 1-MCP and a control. The analysis of nutritional value, enzyme activities and volatile compounds were determined at 3 days interval. The results showed that the MDA content was lower in the fruits treated with 1-MCP compared to the control. The treatment with 1.5 µL L-1 and the control showed the lowest SOD activity compared to the other treatments. POD and CAT were highest in fruits treated with 0.5 µL L-1 compared to control and treatment with 1.0 µL L-1. The 1.5 µL L-1 treatment delayed the decline in vitamin C and protein content compared to the control. Nitrate levels increased 1.34-fold at 0.5 µL L-1 and 2.01-fold in the control. Chlorophyll content degradation was delayed at 1.0 µL L-1 compared to control. Eighty-eight (88) volatile compounds, including terpenes, aldehydes, alkanes, esters, alcohols, acids, phenolic derivatives, ketones and other aromatic compounds, were detected in 'Hangjiao No.2' pepper during the 12-day storage period and treatment concentrations. The production of volatile terpenes was higher in the control than in the 1-MCP treatments, while the 0.5 µL L-1 1-MCP treatment generally suppressed the production of volatile compounds during storage. Overall, the production of volatile compounds after treatment was higher in 'Hangjiao No.2' chili fruits treated with 1.0 µL L-1 1-MCP than in the other treatments throughout the storage period. The results indicate that 1-MCP treatment was more effective in maintaining fruit quality, enhancing the activities of SOD, POD and CAT, retarding the accumulation of MDA and restoring volatile aromas, with 1.0 µL L-1 having the best preservative effect on 'Hangjiao No.2' chili fruit during storage, which could be useful for future marketing and processing.